Place Identity and Community Memory in Louise Erdrich’s the Plague of Doves - Mirzayeva Parvina Ulugbek kizi (Web of Scientist International Scientific Research Journal, 2026)
Drawing on the concept of identity as both a communal and spatial phenomenon, the article examines how the small town of Pluto functions as a central framework through which individual and collective identities are negotiated. Particular attention is given to the narrative perspective of Evelina, whose engagement with family history, memory, and communal relationships illustrates the process of identity formation rooted in place. The paper highlights how genealogical reconstruction and the tracing of historical trauma contribute to a deeper understanding of belonging and selfhood. In addition, the analysis focuses on the character of Shamengwa as a cultural mediator who embodies the transmission of indigenous values, traditions, and collective memory. Through symbolic elements such as music and oral tradition, the novel articulates the interconnectedness of identity, culture, and land. The concept of community is further reinforced through shared experiences, ethical values, and resilience in the face of historical injustice. Ultimately, the article argues that place identity in the novel is not a static construct but a dynamic process shaped by memory, cultural continuity, and social interaction. In this sense, setting transcends its descriptive function and becomes an active force in shaping both individual consciousness and collective existence.